PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS VI SD NEGERI 008 SUMBER JAYA KECAMATAN SINGINGI HILIR - Muhasim Muhasim (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is motivated because the learning outcomes of student Civics education are still very low. Thisstudy aims to improve the learning outcomes of the sixth graders Civics Education SD Negeri 008 Sumber Jaya,Kecamatan Singingi Hilir, Kabupaten Kuantan Singingi. This study uses classroom action research consisting oftwo cycles. Each cycle consists of 4 stages. From the results of the data analysis, the teacher activity in the firstcycle of the meeting got a percentage of 60% and at the second meeting increased to 70%. Cycle II meetingthree, the value of the teacher's presentation was 80% and increased at the fourth meeting to 90%. Studentactivity in the first cycle, got a percentage of 55% and became 65% at the meeting of two cycles I. Cycle IImeeting three, student activity was 80% and became 85% at the fourth meeting. Student learning outcomes areseen from the baseline score, the percentage of completeness is 46.42%, increased after a cycle I daily review of64.28%, in the second cycle daily test student learning outcomes again increased to 85.71% with completecriteria. With the results above, it can be concluded that the application of problem-based learning models canincrease the learning outcomes of Civics Education of SD Negeri 008 Sumber Jaya, Kecamatan Singingi Hilir,Kabupaten Kuantan Singingi.